2022
DOI: 10.3389/fpsyt.2022.846122
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being at Home During Forced Quarantine Amid the COVID-19 Pandemic

Abstract: IntroductionPeople recently or currently in forced quarantine or isolation at home have shown high levels of depression and symptoms of generalized anxiety.Aim of the StudyTo assess the impact of the COVID-19 pandemic on certain aspects of people's day-to-day functioning.Materials and MethodsThe study involved using an online diagnostic survey including a proprietary questionnaire, the DASS 21, and the Liebowitz Social Anxiety Scale.ResultsInformation about the pandemic in Poland and around the world was syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…Levels of fear and threat of coronavirus were significantly higher in younger age groups than in older respondents [24]. In contrast, no relationship between age and severity of anxiety was observed by the authors of another study conducted in Poland [25]. However, it was observed that anxiety affected more than half of the subjects, but the severity of anxiety based on the Liebowitz Social Anxiety Scale was within normal limits.…”
Section: Discussionmentioning
confidence: 70%
“…Levels of fear and threat of coronavirus were significantly higher in younger age groups than in older respondents [24]. In contrast, no relationship between age and severity of anxiety was observed by the authors of another study conducted in Poland [25]. However, it was observed that anxiety affected more than half of the subjects, but the severity of anxiety based on the Liebowitz Social Anxiety Scale was within normal limits.…”
Section: Discussionmentioning
confidence: 70%
“…prał. A. Około-Kułaka, zarejestrowanego i zorganizowanego w 1922 r. 40 w celu kształcenia misjonarzy 41 i wspierania działań na rzecz krzewienia i umacniania wiary katolickiej w Rosji Sowieckiej 42 . Organizacja została zlikwidowana po "kilkuletniej wegetacji" w grudniu 1931 r. 43 ; • Ligi Antybolszewickiej, założonej (w 1920 r.) i kierowanej przez Około-Kułaka 44 , działającej przy wsparciu administracji państwowej 45 .…”
Section: W Warszawieunclassified